Enhancement of anti-tumor efficacy of immune checkpoint blockade by alpha-TEA - Redmond, William L.; Kasiewicz, Melissa J.; Akporiaye, Emmanuel T. (Frontiers in Immunology, 2023)
Cancer immunotherapy such as anti-PD-1/anti-PD-L1 immune checkpoint blockade (ICB) can provide significant clinical benefit in patients with advanced malignancies. However, most patients eventually develop progressive disease, thus necessitating additional therapeutic options. We have developed a novel agent, a-TEA-LS, that selectively induces tumor cell death while sparing healthy tissues, leading to increased activation of tumor-reactive T cells and tumor regression. In the current study, we explored the impact of combined a-TEA-LS + ICB in orthotopic and spontaneously arising murine models of mammary carcinoma. We found that a-TEA-LS + ICB led to increased production of pro-inflammatory cytokines that were associated with a reduction in tumor growth and prolonged survival. Together, these data demonstrate the potential utility of a-TEA-LS + ICB for the treatment of breast cancer and provide the rationale for clinical translation of this novel approach.